Magnesium diboride (MgB2): An effective and novel precursor for the synthesis of vertically aligned BNNTs - Ahmad, Pervaiz; Khandaker, Mayeen Uddin; Muhammad, Nawshad; Rehman, Fida; Khan, Ghulamullah; Khan, Amir Sada; Ullah, Zahoor; Rehman, Muhammad Abdur; Ahmed, Sohail; Gulzar, Mubashar; Din, Israf Ud; Ahmed, Syed Muzamil; et al. (Elsevier, 2018)
Vertically aligned Boron nitride nanotubes (BNNTs) have exceptional electrical, mechanical and thermal properties suitable for its potential applications without any further purification. However, the synthesis of aligned BNNTs via previously reported techniques is not only complicated, lengthy and misleading but also result in useless impurities in the final product. Here, we report Magnesium diboride (MgB2) as an effective and novel precursor for the synthesis of vertically aligned BNNTs directly on SiO2 substrate at 1000 °C. Magnesium (Mg) from MgB2 in partially melted form diffuses on SiO2 substrate whereas the adsorbed Boron with Mg reacts with Nitrogen from decomposed ammonia and synthesized vertically aligned BNNTs. The morphology, alignment, structure and compositions of the as-synthesized BNNTs are studied via field emission scanning electron microscope, high resolution transmission electron microscope, energy dispersive x-ray spectroscopy, x-ray diffraction, Raman spectroscopy and Fourier transform infrared spectroscopy.